Effect of Different Feed Ingredients on the Growth of Caged Common Carp - Rai, Ashok K; Bista, Jaya D (Nepal Agriculture Research Journal, 2011)
To know the effect of four different fish feed, nine months old common carp about 47 g size were stocked at the stocking density of 12 fish m-3 in the cages and cultured in Lake Phewa for 175 days. Four different feed ingredients used were fish meal + soybean + oil cake + rice bran + wheat flour, fish meal + oil cake + rice bran + wheat flour, soybean + oil cake + rice bran + wheat flour and commercial cattle feed. The crude protein ranges from 23 to 32.2%. 32.2% protein content feed containing ingredients of fish meal + soybean + oil cake + rice bran + wheat flour was better for the fish growth (0.30 g day-1) but was the lowest survival rate (65.4%) followed by 27.1% protein content feed containing fish meal + oil cake + rice bran + wheat flour (0.23 g day-1). 26.2% protein content feed containing soybean + oil cake + rice bran + wheat flour without animal protein was the poorest growth rate (0.17 g day-1) with the highest survival rate (95.7%) among the tested feed. It was observed that feed with higher protein level was better for the fish growth and the growth of the fish was different significantly among the treatments except the treatment fish meal + oil cake + rice bran + wheat flour and commercial cattle feed. The common carp fish cultured in cages through artificial feed was not satisfactory. It digs and burrows the pond embankments and sides in search of organic matter that makes pond turbid. Key words: Cage fish culture; Common carp; Feed ingredients DOI: http://dx.doi.org/10.3126/narj.v4i0.4871 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 60-63 Uploaded date: 9 June, 2011